Implementation of Regulatory Impact Analysis as an Instrument of Regulatory Reform Towards the Formation of Quality Legislation within the Framework of the Rule of Law in Indonesia - Parikesit, Satya Bhakti; Herman, KMS (Indonesian Journal of Multidisciplinary Science, 2025)
Public accountants play an important role in ensuring the reliability and transparency of financial reports through an independent and objective audit process. However, in practice, public accountants are often faced with pressure from certain parties that can interfere with their independence and cloud their objectivity. Therefore, legal protection is a crucial aspect to ensure the professionalism and integrity of public accountants in carrying out their duties. This study strives to examine the forms of legal protection available to public accountants in Indonesia, as well as to assess the effectiveness of existing regulations in protecting them from pressure, intimidation, and legal risks that may arise during the audit process. Using a normative legal approach, this study found that although there are various legal provisions governing the public accounting profession, strengthening regulations and protection mechanisms is still needed to ensure that they can work professionally without detrimental intervention.